2013
DOI: 10.1128/aac.00498-13
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Reduced Susceptibility to Quaternary Ammonium Compounds and Bisbiguanides in Clinical Isolates and Laboratory-Generated Mutants of Staphylococcus aureus

Abstract: The MICs and minimum bactericidal concentrations (MBCs) for the biocides benzalkonium chloride and chlorhexidine were determined against 1,602 clinical isolates of Staphylococcus aureus. Both compounds showed unimodal MIC and MBC distributions (2 and 4 or 8 mg/liter, respectively) with no apparent subpopulation with reduced susceptibility. To investigate further, all isolates were screened for qac genes, and 39 of these also had the promoter region of the NorA multidrug-resistant (MDR) efflux pump sequenced. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
87
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 37 publications
8
87
1
Order By: Relevance
“…The only isolate with reduced susceptibility to CHX did not carry qac genes and, on the other hand, isolates carrying qac genes did not reveal high MICs and MBCs. These controversial results have also been observed in other works [15][16][17][18]. However, other studies have reported reduced susceptibility to CHX in strains carrying qacA/B genes [11] and also in strains carrying qacC genes [19].…”
Section: Discussionmentioning
confidence: 59%
“…The only isolate with reduced susceptibility to CHX did not carry qac genes and, on the other hand, isolates carrying qac genes did not reveal high MICs and MBCs. These controversial results have also been observed in other works [15][16][17][18]. However, other studies have reported reduced susceptibility to CHX in strains carrying qacA/B genes [11] and also in strains carrying qacC genes [19].…”
Section: Discussionmentioning
confidence: 59%
“…The QACs resistant genes such as qacA/B, qacC, and smr have been isolated in various environments from clinical CoNS isolates and different Staphylococcal species (13,16). Whereas the current antiseptic MICs related to qac gene positive Staphylococci will not allow survival at in-use concentrations, even moderately increased resistance may allow persistence when residual disinfectants are present (16,22).…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to ethidium bromide and quaternary ammonium compounds can be acquired by the qacC gene. It is usually located on conjugative plasmids in S. aureus and other Staphylococci clinical isolates (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…There is also increasing interest in the incorporation of microbicides into medical devices such as catheters and surgical dressings, with the intention of inhibiting microbial colonization and biofilm formation (34,38,39). Despite the evident benefits of microbicides in the majority of these applications, concerns have been raised that their extensive use may select for bacteria with reduced susceptibility to them or crossresistance to clinically relevant antibiotics (36,40,41). For example, triclosan can select for mutants of A. baumannii that display reduced susceptibilities to multiple antibiotics from chemically distinct classes, in addition to triclosan resistance (42).…”
Section: Discussionmentioning
confidence: 99%